Durability of silorane repair with silorane and methacrylate resin. - Costa, Thays Regina; Cecchin, Lucielle Cristina; Loguercio, Alessandro Dourado; Reis, Alessandra (Brazilian Dental Science, 2014)
Objective: The durability of bonded interface between silorane (SIL) and methacrylate-based (MET) composite resins wasn’t investigated yet. The purpose was to evaluate the repair strength (RS) and nanoleakage of the SIL repair using silorane- or methacrylate-based materials immediately [IM] or after 6 months of water storage [6M]. Materials and Methods: fifteen resin blocks (Filtek P90, 3MESPE) were polished, sandblasted with 50-µm aluminum oxide sandblasting and cleaned with 37% phosphoric acid. Then the specimens were divided into three groups: SIL-SIL (adhesive and composite resin); SIL-MET (silorane adhesive and methacrylate based composite) and MET-MET (methacrylate-based adhesive and composite resin) were used for the repair. Composite-composite bonded sticks (0.9 mm2) were sectioned and divided to be tested in tension (1.0 mm/min) IM or 6M. Two sticks from each tooth, at each time, were immersed in a 50% silver nitrate solution and evaluated by SEM. Data were analyzed by two-way repeated measures ANOVA and Tukey´s tests. Results: The RS of the SIL was not dependent upon the adhesive and composite used for the repair. A significant reduction of the RS was observed for all groups after 6M. Conclusions: Both materials can be used for the repair of the silorane composite, despite degradation occur after 6M.